Public Spending During Growth Accelerations and Decelerations: Exploring the Interaction of the Business Cycle and Control of Corruption - Mendoza, Ronald U (Archīum Ateneo, 2012)
The present paper analyzes the cyclicality of public spending on key social, economic and military sectors, including agriculture, education, health, social protection, transportation and military spending using data available for up to 40 developing countries spanning the period from 1980 to 2004. It utilizes measures of governance as well as indicators for growth acceleration and deceleration episodes to try and tease out possible spending patterns juxtaposed against these conditions. This paper finds evidence that total public spending is largely procyclical during growth decelerations and it is acyclical during growth accelerations. Better governance indicators are also associated with a tempering of this procyclicality of total public spending. In addition, even as total public spending may be procyclical, its subcomponent parts need not be. Finally, military spending tends to be acyclical, suggesting that it neither gets cut nor surges systematically during growth accelerations or decelerations.